Guidelines for the Standard Monitoring of Patients With Thalassemia. Issue 3 (April 2015) - Tubman, Venée N.; Fung, Ellen B.; Vogiatzi, Maria; Thompson, Alexis A.; Rogers, Zora R.; Neufeld, Ellis J.; Kwiatkowski, Janet L.
<x xml:space="preserve">Abstract</x> Chronic transfusion therapy has played a central role in extending life expectancy for patients with hemoglobinopathies such as thalassemia. However, this life-saving therapy is associated with numerous complications that now comprise the bulk of management considerations for patients with thalassemia. This review reports on the experience of the Thalassemia Longitudinal Cohort and reviews available literature to establish guidelines for the management of patients with thalassemia.